The Plant Flow Index: A new method to assess the hydroecological condition of temporary rivers and streams. (January 2021) - Westwood, Christian G.; England, Judy; Hayes, Chloe; Johns, Tim; Stubbington, Rachel
Graphical abstract: Highlights: We assigned weighted scores to 34 common plant taxa based on their response to river drying. We combined the scores to create the Plant Flow Index. PFI was more responsive to recent river drying than existing plant community indices. PFI is unique as an index to characterize plant community responses to river drying. Abstract: Temporary streams are widespread in global river networks, and hydroecological tools are needed to assess biotic responses to changes in environmental conditions between wet and dry states. Plant communities can be abundant and diverse in temporary streams, and vary in their tolerance of changing water availability and associated habitat conditions, but globally, no indices have been developed to document community-level responses to intermittence. We present the first index developed to assess plant assemblage responses to changing habitat conditions in temporary stream channels: the Plant Flow Index (PFI). Using a regional 22-year dataset from lowland groundwater-fed headwater streams in the UK, we establish relationships between the occurrence and abundance of 34 common aquatic, semi-aquatic and terrestrial taxa and the proportion of time the channel was dry within the antecedent 12 months. Species/taxon-specific responses to channel drying were weighted and used to calculate a single score representing each community. We compare the PFI to three other plant assessment methods, which demonstrates its greater ability to reflect the effects of intermittent flow and specifically drying events. The PFI represents a flexible index that can be modified to include additional and/or different taxa and their responses to intermittence, allowing its application across regions and river types with contrasting environmental characteristics and intermittence regimes. As temporary streams increase in both space and time, this index represents a valuable tool to track ecological responses to intermittence at both broad and fine spatial and temporal scales.